Zebrafish (Danio rerio) as a Model for the Study of Developmental and Cardiovascular Toxicity of Electronic Cigarettes - Eman Hussen (18877108) (2023)
The increasing popularity of electronic cigarettes (e-cigarettes) as an alternative to conventional tobacco products has raised concerns regarding their potential adverse effects. The cardiovascular system undergoes intricate processes forming the heart and blood vessels during fetal development. However, the precise impact of e-cigarette smoke and aerosols on these delicate developmental processes remains elusive. Previous studies have revealed changes in gene expression patterns, disruptions in cellular signaling pathways, and increased oxidative stress resulting from e-cigarette exposure. These findings indicate the potential for e-cigarettes to cause developmental and cardiovascular harm. This comprehensive review article discusses various aspects of electronic cigarette use, emphasizing the relevance of cardiovascular studies in Zebrafish for understanding the risks to human health. It also highlights novel experimental approaches and technologies while addressing their inherent challenges and limitations. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms25010194